The Effect of BPJS Kesehatan Participants' Satisfaction on Complaint Handling through the JKN Mobile Application - Muhammad Rafli Aidillah; Muksin Muksin; Andik Supriyatno (Indonesian Journal of Wiyata Health Administration (IJWHA), 2022)
Health services are so complex, including the ability to serve complaints. bpjs kesehatan is a social security for health financing which also accommodates public complaints about health financing services. the purpose of this study is to measure the level of satisfaction in handling complaints from bpjs kesehatan participants through the empathy of officers, the speed of officers, the fairness/fairness of officers, the ease with which participants submit complaints. the results of the study bpjs health participants felt that they had received adequate complaint handling services measured in terms of empathy, speed, fairness and convenience provided in the service. the recommendations offered are still to improve complaint handling services along with the times by accelerating complaint handling, for example through a complaint service on mobile JKN or creating complaint handling outlets in every referral service hospital.